2018
DOI: 10.1159/000494663
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury from Recurrent Heat Stress and Rhabdomyolysis: Protective Role of Allopurinol and Sodium Bicarbonate

Abstract: Background: Heat stress and rhabdomyolysis are major risk factors for the occurrence of repeated acute kidney injury in workers exposed to heat and strenuous work. These episodes, in turn, may progress to chronic kidney disease. Objective: The purpose of this study was to test the effect of allopurinol (AP) and sodium bicarbonate on the kidney injury induced by recurrent heat stress dehydration with concomitant repeated episodes of rhabdomyolysis. Methods: The model consisted of heat stress exposure (1 h, 37°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
13
0
5
Order By: Relevance
“…This is supported by human data demonstrating that the presence of muscle damage increases the risk of AKI during exercise in the heat [36]. These data were recently corroborated in a rodent model of repeated heat exposure, which demonstrated that experimental rhabdomyolysis worsened heat-induced kidney injury [37]. That said, epidemiological data obtained from Guatemalan sugarcane workers indicate that the presence of rhabdomyolysis is not associated with cross-shift declines in kidney function [26], suggesting that the contribution of rhabdomyolysis to progressive reductions in kidney function in this population is likely small.…”
Section: Introductionmentioning
confidence: 64%
“…This is supported by human data demonstrating that the presence of muscle damage increases the risk of AKI during exercise in the heat [36]. These data were recently corroborated in a rodent model of repeated heat exposure, which demonstrated that experimental rhabdomyolysis worsened heat-induced kidney injury [37]. That said, epidemiological data obtained from Guatemalan sugarcane workers indicate that the presence of rhabdomyolysis is not associated with cross-shift declines in kidney function [26], suggesting that the contribution of rhabdomyolysis to progressive reductions in kidney function in this population is likely small.…”
Section: Introductionmentioning
confidence: 64%
“…Finally, sodium citrate, a component in ORS III, is also an effective bicarbonate analog after being metabolized. Since bicarbonate has proved to prevent kidney injury through lowering uric acid levels in heatstroke [31,32], citrate may play a role in preventing AKI. ORS III is crucial to and will benefit EHS rats.…”
Section: Discussionmentioning
confidence: 99%
“…99,100 In addition, according to some studies, sodium bicarbonate delays the progression of CKD 96,101 and one experimental study has demonstrated its protective role in preventing kidney injury from repeated heat stress. 102…”
Section: Treatmentmentioning
confidence: 99%